Clinical Profile, Etiology, and Treatment of Chronic Pancreatitis in North American Women: Analysis of a Large Multicenter Cohort. Issue 7 (August 2016) - Romagnuolo, Joseph; Talluri, Jyothsna; Kennard, Elizabeth; Sandhu, Bimaljit S.; Sherman, Stuart; Cote, Gregory A.; Al-Kaade, Samer; Gardner, Timothy B.; Gelrud, Andres; Lewis, Michele D.; Forsmark, Christopher E.; Guda, Nalini M.; et al.
Abstract : Objective: Historically, chronic pancreatitis (CP) was considered a disease of alcoholic males, but recent data suggest its etiology to be complex. To better understand CP in women, we compared data on women and men with CP in a large, prospectively ascertained multicenter US cohort. Methods: Patients with CP enrolled in the NAPS2 Continuation and Validation study were studied. Information on demographics, etiology, risk factors, phenotype, and treatment(s) used was obtained from detailed questionnaires completed by the patients and physicians. Results: Of 521 cases, 45% were women. Women were significantly ( P < 0.05) less likely to have alcohol etiology (30% vs 58.5%) and more likely to have nonalcoholic etiologies (idiopathic, 32% vs 18%; obstructive, 12% vs 2.4%; genetic, 12.8% vs 7.3%). Demographics, pain experience, morphologic findings, exocrine and endocrine insufficiency, CP-related disability, and use of medical therapies were mostly similar in both sexes. Sphincterotomy (biliary, 33% vs 24%; pancreatic, 38% vs 28%; P < 0.05) was performed more frequently in women, whereas cyst/pseudocyst operations were more common in men (6.6 vs 2.6%, P = 0.02). Conclusions: Most CP cases in women are from nonalcoholic etiologies. In contrast to many other chronic diseases, clinical phenotype of CP is determined by the disease and is independent of sex.